Are environmentally friendly firms more vulnerable during the COVID-19 pandemic?. (25th June 2022) - Zhang, Dengjun; Fang, Yingkai
Abstract: The COVID-19 pandemic has affected supply and demand to a large extent. Declining demand for firms' output has caused significant financial stress for all kinds of firms worldwide. Production that requires environmental measures usually gets constrained when firms, especially small and medium-sized firms (SMEs), have difficulty in accessing credit. Firms thus face the dilemma of whether to continue environmental behaviors or to fulfill financial commitments to suppliers, employees, and so on. As such, an empirical question is whether the economic consequences of COVID-19 vary by firms' types and their environmental behaviors. Using 4, 888 sample firms from 14 EU member states, this study finds evidence that the severity of damage caused by COVID-19 depends on firm size and whether firms invested in pollution abatement techniques. Specifically, eco-friendly firms perform better during the COVID-19 pandemic, and SMEs are less vulnerable than large firms. In particular, eco-friendly SMEs are less affected by the pandemic than conventional SMEs and large firms. These findings are probably related to the efficacy of government relief programs targeted to eco-friendly SMEs and/or the healthy financial status of these firms prior to the pandemic.